Análise reflexiva da produção participativa e da dimensão crítica de materiais de educação ambiental no contexto de bacias hidrográficas no estado de São Paulo - Figueiredo, Andréia Nasser (2013)
Participation, as one of the assumptions of a critical and emancipatory Environmental Education, is essential to promote the meeting of people with different knowledges that create a new knowledge, that is the dialogue.Starting from concrete experiences and seeking to substantiate them, this study aims to understand how the processes of participatory elaboration of materials with the context of Hydrographical Basins contributes to the critical educational process ( involving three dimensions : knowledge, ethical and aesthetic values and political participation ) for the proposed theme and the concept of participation, to contribute to consideration of new processes. From five interviews, the first step to answer our purpose was to analyze the participatory methodological approaches, degrees and concepts of participation and identifiable complex concept Basin in these processes. The development of materials based on the concept of participation is an alternative to overcome the linear view and simplifying the understanding of environmental issues and allows for a critical understanding of the environment and their interrelationships. The socioenvironmental issues may generate a critical and boost the subjects to participate, acting on a broader field, in decision making, as a way of strengthening their citizenship through dialogue in reflective action. The materials bring one of the most prominent themes of the present time, namely the management of water in the context of watersheds or hydrological basins. The holistic concept of basins can help the educational process as a means of integrating the collective. And, in this sense, the materials elaboration through participative methodologies represents a constitutive process to the remaking of the relationship between society and environment, and represents an act of citizen participation. When we understand that the major product of the process is the shaping experience and not only the materials, we understand the importance of encouraging participative methodologies. Furthermore, we believe that a good practice that should be assumed by a/one educator/environmental educator when facing a new process of developing materials based on the evaluation is guided by similar materials. The second stage of the research resulted from analysis of seven materials, resulting from projects systematized interviews, aiming the occurrence of the three dimensions of educational practice which we consider inseparable in an effective work of Environmental Education. The exercise of reflection on past experience provides the teacher/educator the opportunity to learn and not to stumble on the same obstacles encountered by other/the educators/s, thus avoiding presenting the same weaknesses. We understand that this reflection brings methodological contributions to research in environmental education, while, at some point, innovates to analyze and reflect on participation, a concept that permeates the educational action critique, and on the concept and theme Hydrographical Basins. A reflective analysis of the processes of development and some aspects of the materials showed that we deem interesting for the field, and so we gathered in ten guidelines for the participatory preparation of materials to support environmental education. The importance of having guidelines is to support the initiative to the dialogue and to the transforming actions.